2020
DOI: 10.1080/1369183x.2020.1737513
|View full text |Cite
|
Sign up to set email alerts
|

Believing is achieving: a longitudinal study of self-efficacy and positive affect in resettled refugees

Abstract: This paper investigates the link between self-efficacy and positive affect among resettled refugees (N = 180). We hypothesised that self-efficacy would play a key role in improving refugee wellbeing. Research used mixed methods. Alongitudinal survey with three time points confirmed that higher levels of general self-efficacy were consistently associated with better positive affect at later time points. The reverse effects, from positive affect to later selfefficacy, were not significant. In addition, qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
2
23
0
1
Order By: Relevance
“…On top, they are frequently confronted with restrictive migration policies, e.g. with regard to access to labour market, family reunion, or accommodation [ 80 82 ]. Living with so many restrictions without experiencing empowerment or mastery can add to a diminished belief in the ability to achieve desired outcomes and the capacity to exert control [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On top, they are frequently confronted with restrictive migration policies, e.g. with regard to access to labour market, family reunion, or accommodation [ 80 82 ]. Living with so many restrictions without experiencing empowerment or mastery can add to a diminished belief in the ability to achieve desired outcomes and the capacity to exert control [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…with regard to access to labour market, family reunion, or accommodation [ 80 82 ]. Living with so many restrictions without experiencing empowerment or mastery can add to a diminished belief in the ability to achieve desired outcomes and the capacity to exert control [ 82 ]. Low levels of self-efficacy might then, in turn, contribute to poor mental health outcomes, e.g., feelings of embitterment, and impede psychosocial integration even when opportunities arise [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSE can be moderated by age, being a parent, and higher income. Participants with high (CSE) experience mastery during a crisis and consequently, more pleasant emotions than those lower in CSE [29].…”
Section: Predictors Of Emotional Responses During Covid-19mentioning
confidence: 99%
“…Previous research among refugees revealed its positive association with mental health and positive post-migratory outcomes (e.g., employment) [ 25 ]. Additionally, self-efficacy predicted positive affect over a time period of two years among a group of refugees living in the United Kingdom [ 26 ]. An experimental study demonstrated that enhancing self-efficacy led to increased distress tolerance among treatment-seeking refugee torture survivors [ 27 ].…”
Section: Introductionmentioning
confidence: 99%